2019
DOI: 10.1152/ajpgi.00266.2018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gastrointestinal passive paracellular permeability contributes to the obesity-associated hyperoxaluria

Abstract: Most kidney stones (KS) are composed of calcium oxalate and small increases in urine oxalate enhance the stone risk. Obesity is a risk factor for KS, and urinary oxalate excretion increases with increased body size. We previously established the obese ob/ob ( ob) mice as a model (3.3-fold higher urine oxalate) to define the pathogenesis of obesity-associated hyperoxaluria (OAH). The purpose of this study was to test the hypothesis that the obesity-associated enhanced small intestinal paracellular permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Current evidence indicates that obesity accompanied by hyperoxaluria, which is mainly caused by increased oxalate intake due to overeating, can result in increased paracellular absorption from the intestine, and decreased oxalate excretion from the intestine due to inflammation. [ 29,30 ] We also found that GO activity was reduced in aged obese mice. These results suggest that endogenous production of oxalate in our obese model may not make a substantial contribution to hyperoxaluria.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Current evidence indicates that obesity accompanied by hyperoxaluria, which is mainly caused by increased oxalate intake due to overeating, can result in increased paracellular absorption from the intestine, and decreased oxalate excretion from the intestine due to inflammation. [ 29,30 ] We also found that GO activity was reduced in aged obese mice. These results suggest that endogenous production of oxalate in our obese model may not make a substantial contribution to hyperoxaluria.…”
Section: Discussionmentioning
confidence: 66%
“…[ 25,26 ] A study using a mouse model of obesity showed that hyperoxaluria is caused not only by excessive oxalate intake that accompanies overeating but also by enhanced passive gastrointestinal absorption via inflammation‐induced disruption of tight junctions and reduced expression of an oxalate exporter in the ileum. [ 29,30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the intestinal barrier function results in changes in intestinal permeability; Cd exposure has been suggested to down-regulate genes related to enhanced intestinal permeability in the mouse gut, such as tight junction (TJ) genes claudin-1 and occludin [ 43 ]. The disruption of the intestinal barrier function and the increase in intestinal permeability promotes the translocation of toxic luminal substances and pathogenic microorganisms from the intestine into circulation, and this is related to liver injury development [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oxidative stress and chronic inflammation, which are present in all CKD stages, with the highest levels in ESRD (Cobo et al, 2018;Vasylchenko et al, 2020), might themselves contribute to the reduced SLC26A6-mediated transcellular oxalate transport and the enhanced passive paracellular intestinal oxalate absorption (Amin et al, 2018;Bashir et al, 2019;Kumar et al, 2021). In an obese mouse model, oxidative stress and systemic/intestinal inflammation were found to reduce active intestinal oxalate secretion and increase passive intestinal oxalate absorption, eventually resulting in obesity-associated hyperoxaluria (Amin et al, 2018;Bashir et al, 2019). Therefore, this vicious circle of complex molecular mechanisms precludes the accurate determination of the root cause of oxalate dyshomeostasis and its relationship with CVD in patients with ESRD.…”
Section: Gut Microbiota Disruption Causes Hyperoxalemia In Patients With Esrdmentioning
confidence: 99%